2022
DOI: 10.1109/tac.2021.3071953
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Causal Rate-Constrained Sampling of the Wiener Process

Abstract: We consider the following communication scenario. An encoder causally observes the Wiener process and decides when and what to transmit about it. A decoder estimates the process using causally received codewords in real time. We determine the causal encoding and decoding policies that jointly minimize the mean-square estimation error, under the long-term communication rate constraint of R bits per second. We show that an optimal encoding policy can be implemented as a causal sampling policy followed by a causa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Guo and Kostina [9] addressed the estimation of the scalar Wiener and scalar Ornstein-Uhlenbeck processes in the presence of the signaling effect, and obtained a result that matches with that in [8]. They also looked at the estimation of the scalar Wiener process with fixed communication delay in the presence of the signaling effect in [10], and obtained a similar structural result. Furthermore, Sun et al [11] studied the estimation of the scalar Wiener process with random communication delay by discarding the signaling effect, and showed that the optimal triggering policy is symmetric threshold.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Guo and Kostina [9] addressed the estimation of the scalar Wiener and scalar Ornstein-Uhlenbeck processes in the presence of the signaling effect, and obtained a result that matches with that in [8]. They also looked at the estimation of the scalar Wiener process with fixed communication delay in the presence of the signaling effect in [10], and obtained a similar structural result. Furthermore, Sun et al [11] studied the estimation of the scalar Wiener process with random communication delay by discarding the signaling effect, and showed that the optimal triggering policy is symmetric threshold.…”
Section: Introductionmentioning
confidence: 77%
“…This leads to the employment of the linear-quadratic regulator with a state estimate at the controller without the signaling residual. More specifically, we have u k = −L k xk , where L k = (B T S k+1 B + R) −1 B T S k+1 A is the linear-quadratic regulator gain, xk is a state estimate at the controller satisfying (10) with ı k = 0 for all k ∈ K, and S k 0 is a matrix that satisfies the algebraic Riccati equation…”
Section: Lemmamentioning
confidence: 99%
See 1 more Smart Citation
“…packet-erasure channel in [5], [6], remote estimation of a scalar Markov process with symmetric noise distribution over an ideal channel in [9], remote estimation of a scalar autoregressive Markov process with symmetric noise distribution over an ideal channel, an i.i.d. packet-erasure channel, and a Gilbert-Elliott packeterasure channel in [10]- [12], remote estimation of the scalar Wiener and scalar Ornstein-Uhlenbeck processes over an ideal channel and a fixed-delay channel in [13], [14], remote estimation of the scalar Wiener process over a random-delay channel in [15], remote estimation of multiple random variables with arbitrary distributions over a collision channel in [16], [17], remote estimation of multiple random variables with arbitrary distributions over unicast and broadcast channels in [18], and remote estimation of two Gaussian random variables over a multi-access channel in [19]. These studies established certain characteristics such as a symmetric, asymmetric, or threshold structure of the optimal scheduling policy with respect to the estimation discrepancy.…”
Section: A Related Workmentioning
confidence: 99%